AVALIAÇÃO DOS ÍNDICES DE EFICIÊNCIA NUTRICIONAL DE MATRIZES NELORE EM SISTEMA EXTENSIVO - DORNA, Laynne Ribeiro; LIMA, Josilaine Aparecida da Costa; BORGES, Gabriel de Lima; CARMO, Jéssica Soares; FERNANDES, Henrique Jorge (ANAIS DO ENIC, 2020)
-